History and functions of underground spiritual mosques in Kazakhstan (in written and archaeological sources) (Journal of history, 2021)
The article is devoted to the history and functions of underground spiritual mosques in Kazakhstan. The sources are the works of medieval travelers, chroniclers and Turkish, Russian scientists, domestic and foreign researchers, as well as archival documents written about Shakpak Ata, Ulken Kyluet, Shildekhan, Kumshik Ata, Imam Markozy, Beket Ata and other underground mosques. The study analyzes the records and archaeological data on underground mosques built and functioning in the 9th - 20th centuries on the Kazakh land. To determine the object of research, methods of comparison, forecasting, analysis were used, aimed at disclosing the content of historical data and formulated facts. The scientific results of the article will supplement our historical knowledge and reveal the religious and spiritual history of our people to the younger generation.It can also be used to develop religious and spiritual tourism in the country.